Geochemical shifts, ecological consequences, and onset of meromixis in a mine water impacted boreal lake - Kehusmaa, Karoliina; Tammelin, Mira; Kauppila, Tommi; Österholm, Peter; Saarni, Saija (Springer Science and Business Media LLC, 2026)
Mine waters are often severely detrimental to nearby waterbodies and can even disturb the circulation regime of a lake. We investigated the recent sediment record of a small, presently meromictic lake, which receives sulphate and metal-rich waters from a closed polymetal mine. We wanted to examine the overall impacts of mining on the lake and detect the onset and development of meromixis. Our hypothesis was that the loading from the mine would lead to notable geochemical and palaeoecological changes, and that we could identify the shift in the circulation regime using multiple proxies. We cored the deepest part of the lake and obtained discrete samples for the geochemical and diatom analyses. We detected clear shifts corresponding to the periods before, during, and after mining in the main proxies. Sulphur and metalloids associated with acid mine drainage increased during mining, and the dominant cyclotelloid species changed in the diatom assemblage. The onset of meromixis seems to have occurred during the closure of the mine in late 1980s as the redox conditions in the tailings changed. Our findings highlight the impacts of saline mine waters on lake circulation, and the wide-ranging consequences of releasing mine waters into the aquatic environment.